(untitled) (Eurasian Scientific Herald, 2022)
Siding" retains its qualities and original appearance for many years. It perfectly protects the building from the effects of atmospheric phenomena. This is a very light, easy-to-use material that looks great. This type of finishing material is made of wood. It differs in the method of processing the wood and the type of section of the finished panel.